Students’ attitudes towards statistics Field study on a sample of students of the Department of Social Sciences, Ibn Khaldun Tiaret University - brakhlia, abdelghani; barkat, abdelhak (Journal of Social Sciences and Humanities, 2020)
This study aimed at identifying the attitudes of Iben khaldoune University students towards statistics, because we have noticed through our teaching of this subject over several years, the presence of some misconceptions about this subject, and to achieve the goals of the study, the researchers relied on the steps of the descriptive approach, and a random sample of 100 male and female students was divided into three specializations in the second phase (Master) during the 2016/2017 academic year. The researchers also adopted the scale of attitudes toward statistics, relying on the scale prepared by Al-Smadi (2008), and some foreign and other Arab standards. The scale consists in its final form of 38 words distributed on five dimensions, which are after students' direction towards their performance in the subject of statistics, and after realizing the importance of Statistics, after fun, and after the teacher's impact on students, and after the future need for statistics, and the psychometric properties of the tool were confirmed and then applied to the study sample. Based on the Statistical Package for Social Sciences program, study data was analyzed with a set of appropriate statistical methods, The results indicated positive trends prevailing among students towards the subject of statistics at the dimension of the tool The overall degree, as the results indicated that there are no differences between males and females in their attitude towards statistics, while there are statistically significant differences among the sample members in their direction towards statistics attributable to the variable of the baccalaureate division in favor of the science division.